Procedural sedation with dexmedetomidine for ultrasound guided central venous cannulation in agitated, high risk critically ill patients. A series of three cases - Shrestha, Gentle S; Parajuli, Bashu Dev; Bhattarai, Amit Sharma (Bangladesh Critical Care Journal, 2017)
Central venous cannulation is a commonly performed procedure in ICU. Even in the experienced hands, it is not free of complications. Acute mechanical adverse events are more likely in agitated and uncooperative patients. Ultrasound guided cannunation of internal jugular vein is associated with higher success rate and fewer mechanical complications when compared with traditional techniques. Dexmedetomidine has been used as a safe and effective agent for procedural sedation in a wide variety of patients. Here we successfully used dexmedetomidine for ultrasound guided central venous cannulation of internal jugular vein in uncooperative high risk patients, even at the extremes of age. Bangladesh Crit Care J March 2017; 5(1): 68-69